2020
DOI: 10.1038/s41598-020-66161-z
|View full text |Cite
|
Sign up to set email alerts
|

A single Proteus mirabilis lineage from human and animal sources: a hidden reservoir of OXA-23 or OXA-58 carbapenemases in Enterobacterales

Abstract: In Enterobacterales, the most common carbapenemases are Ambler’s class A (KPC-like), class B (NDM-, VIM- or IMP-like) or class D (OXA-48-like) enzymes. This study describes the characterization of twenty-four OXA-23 or OXA-58 producing-Proteus mirabilis isolates recovered from human and veterinary samples from France and Belgium. Twenty-two P. mirabilis isolates producing either OXA-23 (n = 21) or OXA-58 (n = 1), collected between 2013 and 2018, as well as 2 reference strains isolated in 1996 and 2015 were ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Intriguingly, the genomes of 20 OXA-23-producing P. mirabilis isolates recovered from France and Belgium have been compared to all Proteus genomes available in the NCBI database. This study highlighted that all isolates belonged to a single lineage that has spread since 1996 ( 126 ). Moreover, veterinary samples were included in this study and revealed that this lineage has spread also in animals ( 126 ).…”
Section: Minor Class D Carbapenemasesmentioning
confidence: 91%
See 3 more Smart Citations
“…Intriguingly, the genomes of 20 OXA-23-producing P. mirabilis isolates recovered from France and Belgium have been compared to all Proteus genomes available in the NCBI database. This study highlighted that all isolates belonged to a single lineage that has spread since 1996 ( 126 ). Moreover, veterinary samples were included in this study and revealed that this lineage has spread also in animals ( 126 ).…”
Section: Minor Class D Carbapenemasesmentioning
confidence: 91%
“…This study highlighted that all isolates belonged to a single lineage that has spread since 1996 ( 126 ). Moreover, veterinary samples were included in this study and revealed that this lineage has spread also in animals ( 126 ). Analysis of the genetic context revealed that the bla OXA−23 gene is mainly carried on the chromosome of P. mirabilis ( 122 , 124 , 127 ) except for one isolate from France and three isolates from Singapore.…”
Section: Minor Class D Carbapenemasesmentioning
confidence: 91%
See 2 more Smart Citations
“…Among the genes found within these modules are bla OXA-58 ; the bla OXA-143 -like bla OXA-253 ; the tetracycline resistance gene tet39 ; the macrolide resistance genes msrE and mphE ; the chromium resistance genes chrA and chrB ; the organic hydroperoxide resistance genes ohr/ohrR ; the transport-related genes, such as sulP and kup ; the tellurium resistance terC ; and toxin-antitoxin ( add ) genes [ 19 , 23 , 26 , 29 , 30 , 31 ]. Some of them, like ohr/ohrR , chrA , chrB , sulP , kup , and add , were found in different Acinetobacter species [ 30 ], and bla OXA-58 was found in Proteus mirabilis [ 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%